MRI on a new polymeric multichannel membrane for ultrafiltration - Kern, Stefanie; Lerner, Rahel; Schork, Nicolas; Nirschl, Hermann; Heijnen, Martin; Guthausen, Gisela (Frontiers in Chemical Engineering, 2023)
Membrane ultrafiltration in new polymeric multi-channel membranes designed for in-out filtration was investigated to get insights into structure, flow and filtration properties. In-situ magnetic resonance imaging (MRI) allows non-invasive and non-destructive investigations with adequate spatial and time resolution. The structure of the new polymeric membrane was measured with an in-plane spatial resolution of 35 µm/pixel revealing first the polymer density distribution over the 19-channel membrane and second the wettability of the fiber and its cavities of different dimensions. MRI was also used to answer questions about flow and consequently feed distribution in the channels. Finally, in-situ filtration of an aqueous solution of sodium alginate was observed which led to deposit formation at the channel’s inner surfaces. The kinetics of this deposit formation was quantified. Backwashing and flushing gave insight into the cleanability of the channels.